Serum Magnesium in Pre-eclampsia and Eclampsia (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Objective: To assess the serum magnesium level of pregnant women with pre-eclampsia and eclampsia in Mymensingh Medical College & Hospital (MMCH).   Materials and Methods: This descriptive cross-sectional study was carried out in the   department of Obstetrics and Gynaecology of Mymensingh Medical College & Hospital (MMCH) and Prof. Muhammed Hossain Central Laboratory of Bangladesh Agricultural University (BAU). The serum magnesium level were estimated in 60 study subjects who were pregnant   women with pre-eclampsia & eclampsia and of 60 control subjects who were the normotensive pregnant women by photometric test using xylidyl blue.   Results: The mean (±SD) serum magnesium of the control and study group were (2.29 ± 0.28 mg/dl) & (1.84 ±0.26 mg/dl) respectively. The difference in serum magnesium level between the two groups was statistically highly significant (p=